Perancangan Sistem Diagnosa Penyakit Pada Ayam Menggunakan Metode Certainty Factor Peternakan Ayam Parude Rude - Safrizal, Edy; Juhardi, Ujang; Khairullah, Khairullah; Wibowo, Sastya Hendri (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
Indonesia as a tropical and agricultural country, has various types of flora and fauna, one of which is chicken, chicken is one of the most widely farmed poultry because of its many benefits and advantages. As with other livestock, chicken has various types of diseases. For some farmers who want to raise chickens, especially lay people, they are faced with several problems, one of which is disease.One of the factors that causes losses is the lack of knowledge of farmers about diseases that attack chickens and how to treat them. Therefore, in this study, a web-based expert system application will be created to provide information about diseases and symptoms in chickens, as well as provide solutions and treatments using the Certainty Factor method.The use of this certainty factor method is to describe the level of confidence in the problem. The data needed in designing this expert system application are disease data, symptom data, and solution data on how to handle it.